Sézary Syndrome and Atopic Dermatitis: Comparison of Immunological Aspects and Targets. (17th May 2016) - Saulite, Ieva; Hoetzenecker, Wolfram; Weidinger, Stephan; Cozzio, Antonio; Guenova, Emmanuella; Wehkamp, Ulrike
Abstract : Sézary syndrome (SS), an aggressive form of erythrodermic pruritic cutaneous T cell lymphoma (CTCL), from an immunological perspective characterized by increased Th2 cytokine levels, elevated serum IgE and impaired cellular immunity. Not only the clinical appearance but also the hallmark immunological characteristics of SS often share striking similarities with acute flares of atopic dermatitis (AD), a common benign chronic inflammatory skin disease. Given the overlap of several immunological features, the application of similar or even identical therapeutic approaches in certain stages of both diseases may come into consideration. The aim of this review is to compare currently accepted immunological aspects and possible therapeutic targets in AD and SS.